Assessment of marine protected areas in the East China Sea using a management effectiveness tracking tool - Chen, Mingyang; Zeng, Cong; Zeng, Xu; Liu, Yue; Wang, Zihan; Shi, Xiaojing; Cao, Ling (Frontiers in Marine Science, 2023)
Marine protected areas (MPAs) are important tools for maintaining biodiversity, mitigating climate change, and conserving and restoring natural ecosystems. Management effectiveness assessment is an important component of conservation management in protected areas. In this study, we constructed a management effectiveness assessment tool based on publicly available information for China, with a total score of 126. We used the tool to systematically assess 27 national MPAs in the East China Sea. Our results showed that marine nature reserves (MNRs) and marine special reserves (MSRs) could be classified into two and three classifications, respectively, including MNRs I (n = 4, scores = 88-100), MNRs II (n = 6, scores = 75-81), MSRs I (n = 8, scores = 75-90), MSRs II (n = 6, scores = 59-75) and MSRs III (n = 3, scores = 53-56). Factors influencing the management effectiveness of nature reserves were the length of establishment and general public budget revenue, while for special reserves they were the length of establishment and total agricultural output value. Furthermore, protected areas with high management effectiveness scores tend to have a longer establishment time, dedicated management departments, adequate management staff and financial investment compared to those with low scores. In addition, the low-score MPAs require more communication with stakeholders. The study provides an objective and comprehensive systematic scoring of MPAs’ management using METT-based framework and multi-source data. It overcomes the challenge of the general lack of data on MPAs and provides a new approach to management effectiveness assessment.